Formation and morphology of dark puffs in Drosophila melanogaster polytene chromosomes. - Semeshin, V.F.; Shloma, V.V.; Zhimulev, I.F. (Hereditas, 2001)
The formation of unusual dark puffs in Drosophila melanogaster polytene chromosomes has been studied by electron microscopic (EM) analysis. Fly stocks transformed by the P[ry; Prat:bw] and P[hs-BRC-z1] constructs were used. In the former the bw gene is under the promoter of a housekeeping gene, Prat; in the latter the Br-C locus, mapping to the dark puff 2B, is under the promoter of a heat-shock gene, hsp70. Inserted into region 65A of the 3L chromosome, the Prat:bw copies give rise to structures which are morphologically reminiscent of the so-called "dark" puffs. In contrast, insertion of P[hs-BRC-z1] into region 99B of the 3R chromosome causes a regular "light" puff of form. Comparative analysis of the dark puffs--both transgenic and natural--suggests that there might be at least two mechanisms underlying their formation. One is a local incomplete decondensation of activated bands, characteristic of the so-called small puffs. The other is the formation of ectopic-looking contacts between the bands adjacent to the puffing zone. Transposition of the DNA, from which such a puff develops, causes a regular light puff to form at the new location. Heterochromatic regions do not appear to be directly involved in puffing.